2017
DOI: 10.3892/ol.2017.6021
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA C22orf32-1 contributes to the tumorigenesis of nasopharyngeal carcinoma

Abstract: Abstract. The mechanism of nasopharyngeal carcinoma (NPC) remains unclear. The present study investigated the abnormal expression of long non-coding (lnc)RNAs in NPC tissues and one NPC cell line to identify the involvement of lncRNAs in the tumorigenesis of NPC. Using a quantitative reverse transcription polymerase chain reaction (RT-qPCR), the expression of lncRNA C22orf32-1 in NPC tissues and an NPC cell line was verified. The effects of lncRNA C22orf32-1 on NPC cells were investigated with a cell prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…A growing number of studies have indicated that lncRNAs can determine some cellular processes in cancer, including proliferation, metastasis, and differentiation (Eades et al, ; Jiang et al, ). Many earlier studies have presented that lncRNAs are associated with carcinogenesis, metastasis, prognosis, and diagnosis, and function as oncogenes or cancer suppressor genes (Chen et al, ; Jen et al, ; Nie et al, ). Herein, more studies are required to elucidate the biological and molecular mechanisms of lncRNAs on cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have indicated that lncRNAs can determine some cellular processes in cancer, including proliferation, metastasis, and differentiation (Eades et al, ; Jiang et al, ). Many earlier studies have presented that lncRNAs are associated with carcinogenesis, metastasis, prognosis, and diagnosis, and function as oncogenes or cancer suppressor genes (Chen et al, ; Jen et al, ; Nie et al, ). Herein, more studies are required to elucidate the biological and molecular mechanisms of lncRNAs on cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In this content, it has been reported that several lncRNAs are related with NPC pathogenesis. For instance, lncRNA-LINC00460 facilitated NPC tumorigenesis through sponging miR-149-5p to up-regulate IL-6 (10) , lncRNA FAM226A promoted NPC tumorigenesis and metastasis by acting as ceRNA to sponge miR-590-3p/miR- 1275 and up-regulate ITGB3 (17) , lncRNA HOTAIR contributed to the tumorigenesis of NPC via up-regulating FASN (11) , lncRNA LINC01133 mediated NPC tumorigenesis by binding to YBX1 (15) , lncRNA C22 or f32-1 contributed to the tumorigenesis of NPC (12) , lncRNA PXN-AS1-L promoted the malignancy of NPC cells via up-regulation of SAPCD2 (13) , and the lncRNA PVT1 regulated NPC cell proliferation via activating the KAT2A acetyltransferase and stabilizing HIF-1a (14) . Consistent with these previous reports, in the current study, we demonstrated that suppression tumor suppressors in variety kinds of cancers (23) .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several lncRNAs including EWSAT1 (9) , LINC00460 (10) , HOTAIR (11) , C22orf32-1 (12) , PXN-AS1-L (13) , PVT1 (14) , LINC01133 (15) , DANCR (16) , and FAM225A (17) haven been reported to be associated with NPC tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, studies have uncovered the role of lncRNAs in carcinogenesis, suggesting that these genes may be used as promising biomarkers in cancer ( 4 6 ). Among them, lncRNA ANRIL is associated with an unfavorable prognosis and aggravates invasion in malignant OC ( 5 ), whereas lncRNA homeobox (HOX) A11-antisense suppresses the oncogenic phenotype of epithelial OC ( 6 ).…”
Section: Introductionmentioning
confidence: 99%